2021
DOI: 10.3389/fmars.2021.699000
|View full text |Cite|
|
Sign up to set email alerts
|

Distribution Patterns of Floating Microplastics in Open and Coastal Waters of the Eastern Mediterranean Sea (Ionian, Aegean, and Levantine Seas)

Abstract: Microplastic pollution is a pervasive anthropogenic phenomenon at the ocean surface. Numerous studies have been performed worldwide; nevertheless, the distribution patterns, morphological properties, and sources of origin in the Eastern Mediterranean Sea are still poorly explored. The purpose of this study is to investigate the distribution patterns of surface floating microplastics (MPs) in the Ionian, Aegean, and Levantine Seas in relation to their sources and sea surface circulation. In total, eighty-four s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 88 publications
(114 reference statements)
6
10
0
Order By: Relevance
“…All of them were characterized for their shape and size (Figure 12). The majority of particles found were characterized as fragments that result to be the dominant shape independently of seasonal campaign and sampling area, in agreement with several studies on MPs, collected in similar regions of the Mediterranean, including the Ligurian Sea, Gulf of Lion, Gabes, and Saronikos Gulf (Fossi et al, 2017;Schmidt et al, 2018;Tziourrou et al, 2019;Zayen et al, 2020;Adamopoulou et al, 2021). The high prevalence of fragments in surface water suggests that the microplastics derived from degradation of waste, originating from population activities, especially in proximity of densely populated coastal areas, either through rivers or landfills (Collignon et al, 2012;Pedrotti et al, 2016;Schmidt et al, 2018;Simon-Sánchez et al, 2022).…”
Section: Microplastics Properties Variabilitysupporting
confidence: 90%
See 3 more Smart Citations
“…All of them were characterized for their shape and size (Figure 12). The majority of particles found were characterized as fragments that result to be the dominant shape independently of seasonal campaign and sampling area, in agreement with several studies on MPs, collected in similar regions of the Mediterranean, including the Ligurian Sea, Gulf of Lion, Gabes, and Saronikos Gulf (Fossi et al, 2017;Schmidt et al, 2018;Tziourrou et al, 2019;Zayen et al, 2020;Adamopoulou et al, 2021). The high prevalence of fragments in surface water suggests that the microplastics derived from degradation of waste, originating from population activities, especially in proximity of densely populated coastal areas, either through rivers or landfills (Collignon et al, 2012;Pedrotti et al, 2016;Schmidt et al, 2018;Simon-Sánchez et al, 2022).…”
Section: Microplastics Properties Variabilitysupporting
confidence: 90%
“…The MPs abundance (mean = 0.8 × 10 5 items/km 2 during spring 2019 and 4.7 × 10 4 items/km 2 during autumn 2019), obtained from sampling in Saronikos Gulf, fall in the same range with outputs from campaigns during 2015 and 2016 (3.5 × 10 2 items/km 2 -9.2 × 10 5 items/km 2 ) (Adamopoulou et al, 2021). Interestingly, in the latter study, the maximum MPs concentration for the Aegean and Ionian Seas was not found in areas in the proximity of the anthropogenic sources, suggesting that the relationship between them is not easily predictable.…”
Section: Saronikos Gulfmentioning
confidence: 59%
See 2 more Smart Citations
“…Next, we compare our findings with previous 2017) measured 0.19-7.73 counts/m 3 in the Stockholm Archipelago, and 0-0.8 counts/m 3 were found in the GOF (Setälä et al, 2016). In the Arctic waters, Lusher et al (2015) revealed MP concentrations of 0-1.31 counts/m 3 , 0.07-9.25 counts/ m 3 were measured in the Eastern Mediterranean Sea (Adamopoulou et al, 2021), 1.82 counts/m 3 were observed in the Mediterranean Sea (Zeri et al, 2018), and 0.06-25.9 counts/m 3 were found in the Eastern Indian Ocean (Li et al, 2021).…”
Section: Discussionsupporting
confidence: 68%